The BIBB Training Panel - An Establishment Panel on Training and Competence Development - Gerhards, Christian [Verfasser]; Mohr, Sabine [Verfasser]; Troltsch, Klaus [Verfasser] (My University, 2012)
Establishments play a key role in Germany`s working age population, be it as apprentices in the dual VET or later in the world of work, when establishments offer continuing training programs. All in all, establishments create integrated opportunities for their staff to acquire qualifications and competencies. In order to study training opportunities, BIBB has been carrying out an Establishment Panel on Training and Competence Panel, the so-called BIBB Training Panel. Long-term data on training activities in Germany`s establishments are recorded. In its initial phase, the Training Panel has been financed by the Federal Ministry of Education and Research for three years and is conducted jointly by BIBB together with TNS Infratest, a market research company. A general aim of the Training Panel was the creation of a long-term database with information on establishment training and competence development in Germany. The structure of this document is the following: The general aims of the Training Panel - Summary of the statistical population and sampling requirements, explanation of technical terms - Technical information on questionnaires, field study phase and data editing - Access and data security - Conclusion: future tasks and forecast. (BIBB-Doku)

Betriebe haben sowohl für die berufliche Erstausbildung als auch für die berufliche Weiterbildung einen hohen Stellenwert. Zu deren Untersuchung soll das BIBB-Qualifizierungspanel dienen, das 2011 startete, vom BMBF für die ersten drei Jahre finanziert und in Kooperation mit TNS Infratest durchgeführt wird. Hauptziel des Panels ist eine auf lange Sicht angelegte Datenbank mit Informationen zur betrieblichen Bildung und Kompetenzentwicklung. Gegenstand des Beitrags sind die Hauptziele des Panels, Untersuchungsgegenstände, technische Informationen zum Fragebogen, Phasen der Feldstudien und Umgang mit Daten, Zugang und Datensicherheit. Künftige Aufgaben und ein Ausblick beschließen den Beitrag. (BIBB-Doku)
Das BIBB-Qualifizierungspanel: Ein Betriebspanel zu Ausbildung und Kompetenzentwicklung
Keywords: G 1.3.1 Bildungsangebot & -nachfrage; T 3.5 Statistik; BIBB-Qualifizierungspanel; Ausbildungsbeteiligung; Weiterbildungsbeteiligung